1992
DOI: 10.1111/j.1399-0039.1992.tb01918.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DP antigen and Takayasu arteritis

Abstract: Sixty-four patients with Takayasu arteritis and 317 healthy individuals in the Japanese population were examined for HLA-A, -B and -C alleles by serological typing and for HLA-DR, DQ and DP alleles by DNA typing using PCR/SSOP analysis. The frequencies of HLA-Bw52, DRB1*1502, DRB5*0102, DQA1*0103, DQB1*0601 and DPB1*0901 alleles were significantly increased and the frequencies of HLA-Bw54, DRB1*0405, DRB4*0101, DQA1*0301, DQB1*0401 alleles were significantly decreased. Strong linkage disequilibria among the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 27 publications
(25 reference statements)
0
22
1
Order By: Relevance
“…For example, the major genetic contribution to rheumatoid arthritis involves DRB1 alleles such as *0401 and *0404 (27), whereas HLA-DQ alleles, especially DQ2 and DQ8, provide the major genetic contribution to type 1 diabetes (26). Certain DP alleles also have been implicated as genetic susceptibility alleles for pauci-articular juvenile chronic arthritis (28), Graves disease (29), and Takayasu's arteritis (30). One central hypothesis for the increased susceptibility to disease is that the associated class II molecule preferentially presents a critical epitope to disease-relevant T cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the major genetic contribution to rheumatoid arthritis involves DRB1 alleles such as *0401 and *0404 (27), whereas HLA-DQ alleles, especially DQ2 and DQ8, provide the major genetic contribution to type 1 diabetes (26). Certain DP alleles also have been implicated as genetic susceptibility alleles for pauci-articular juvenile chronic arthritis (28), Graves disease (29), and Takayasu's arteritis (30). One central hypothesis for the increased susceptibility to disease is that the associated class II molecule preferentially presents a critical epitope to disease-relevant T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of autoimmune diseases have been associated with HLA-DP. [4][5][6][7][8] HLA-DP-restricted virus, 9 bacterial, 10 or tumor 11 antigenspecific T cells have been described. HLA-DP has also been shown to be capable of presentation of HLA-A1 or HLA-DR3-derived allopeptides for indirect allorecognition by HLA-DP-restricted alloreactive CD4 ϩ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] In the Japanese population, the HLA-B52 and -B39 haplotypes are closely associated with susceptibility to TA. 15, 16 In addition, it has been suggested that the presence of specific HLA-B alleles is related to clinical manifestations of TA.…”
Section: Editorial P 1591mentioning
confidence: 99%